2010
DOI: 10.1007/978-1-4419-5786-3_10
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Nanoporous Membranes for Immunoisolated Cell-Based Drug Delivery

Abstract: Materials advances enabled by nanotechnology have brought about promising approaches to improve the encapsulation mechanism for immunoisolated cell-based drug delivery. Cell-based drug delivery is a promising treatment for many diseases but has thus far achieved only limited clinical success. Treatment of insulin dependent diabetes mellitus (IDDM) by transplantation of pancreatic β-cells represents the most anticipated application of cell-based drug delivery technology. This review outlines the challenges invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 101 publications
0
9
0
Order By: Relevance
“…Such devices could reduce the risk of immunorejection of grafts without the requirement of immunosuppressive drug therapies. Moreover, such devices can potentially include provascularization factors or even be prevascularized prior to implantation in order to help circumvent the loss of graft mass due to inadequate oxygen supply . Such approaches are not necessarily new and indeed have been the focus of many commercial exploits over the years.…”
Section: Islet Transplantation and New Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such devices could reduce the risk of immunorejection of grafts without the requirement of immunosuppressive drug therapies. Moreover, such devices can potentially include provascularization factors or even be prevascularized prior to implantation in order to help circumvent the loss of graft mass due to inadequate oxygen supply . Such approaches are not necessarily new and indeed have been the focus of many commercial exploits over the years.…”
Section: Islet Transplantation and New Therapeutic Approachesmentioning
confidence: 99%
“…Such approaches are not necessarily new and indeed have been the focus of many commercial exploits over the years. Prominent examples include work by Newgard and colleagues in a joint effort with Gore Hybrid Technologies which generated chambers suitable for the implantation of immortal pancreatic beta‐cell xenografts into mouse models . Similarly, in 1999, Baxter Healthcare also reported success using a comparable apparatus, also to implant immortal xenogeneic beta‐cells in NOD mice .…”
Section: Islet Transplantation and New Therapeutic Approachesmentioning
confidence: 99%
“…Encapsulated MIN-6 cells were shown to be responsive to different glucose concentrations, while IgG diffusion was significantly diminished. Titania porous membranes have been fabricated, and also benefit from tight nanometer pore size distributions, but unfortunately were not mechanically robust [272]. In a composite approach, Randall et al demonstrated that gold-coated self-folding porous membranes, made by lithographic patterning, could exhibit precisely controlled pore sizes based on the gold deposition duration (Fig.…”
Section: Cell Penetration Restrictive Devicesmentioning
confidence: 99%
“…have developed a microfabricated membrane that can be incorporated into a device that both limits immune cell signaling and allows for adequate diffusion ( Fig. 18.2 ) ( [ 7,91,122,123,130 ] ). Nano-channels on the surface of the membrane allow for quick diffusion of glucose and other nutrients, yet inhibit transport of antibodies.…”
Section: Cell-based Drug Delivery Therapymentioning
confidence: 99%